`We support football in our heart`: female football fandom in Iran - Eskandari, Z. T. (Soccer & Society, 2022)
Despite the growing research regarding sports fandom culture, the related knowledge concerning non-West female fans, specifically Muslim women, is next to absent. By drawing on gender theories alongside transnational feminism, this study critically investigates the experiences and practices of female football fans in Iran, a country with exclusive social features. Through semi-structured interviews, 25 women and 5 men talked about their lived experiences. Findings suggest that the female fandom stream is empowering, although female fans still have to overcome gender stereotypes to demonstrate the authenticity of their fandom. Also, the state still restricts female activities in different ways, such as stadium entrance ban and shortage of media coverage. However, women have followed their desires and applied strategies to remain fans and support their teams afar. In this way, alongside multiple practical opportunities, they have converted social media to a virtual stadium to demonstrate both their support and consent.